The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1038/s41598-021-87447-w
|View full text |Cite
|
Sign up to set email alerts
|

Gender-specific differences in feasibility of pre-lacrimal window approach

Abstract: The feasibility and surgical effort of a pre-lacrimal window approach (PLWA) depends on the width of the bony window anterior to the nasolacrimal duct. This study aimed to investigate gender-specific differences in feasibility of PLWA. A consecutive series of paranasal computed tomography scans from 50 females (n = 100) and 50 males (n = 100) were retrospectively analyzed. The primary outcome measure was the antero-posterior length of the bony pre-lacrimal window (BPLWA). The secondary outcome measure was the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 16 publications
(8 reference statements)
0
5
0
Order By: Relevance
“…2). The mean CT scan score was Ragab and Abo El Naga The Egyptian Journal of Otolaryngology (2022) 38:141 11 with a range (of [3][4][5][6][7][8][9][10][11][12][13][14]. An endoscopic assisted minimal sublabial approach was used [4 patients (67%)] for central lesions (cysts originating from the medial incisors with expansion only into the nasal cavity floor) [1 patient (17%)], as well as for cysts originating from the canines (elevating the nasal and antral floors) [1 patient (17%)], extension below the level of the nasal floor and lateral expansions and extensions with or without scalloping of the anterior wall of the maxillary bones [2 patients (33%)].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2). The mean CT scan score was Ragab and Abo El Naga The Egyptian Journal of Otolaryngology (2022) 38:141 11 with a range (of [3][4][5][6][7][8][9][10][11][12][13][14]. An endoscopic assisted minimal sublabial approach was used [4 patients (67%)] for central lesions (cysts originating from the medial incisors with expansion only into the nasal cavity floor) [1 patient (17%)], as well as for cysts originating from the canines (elevating the nasal and antral floors) [1 patient (17%)], extension below the level of the nasal floor and lateral expansions and extensions with or without scalloping of the anterior wall of the maxillary bones [2 patients (33%)].…”
Section: Resultsmentioning
confidence: 99%
“…Access to lesions at the anterior wall and alveolar recess of the maxillary sinus is challenging. Possible endoscopic options are the application of a 70° endoscope following a type III sinusotomy, endoscopic standard medial maxillectomy, endoscopic pre-lacrimal window approach (PLWA), Endoscopic endonasal minimal rhinotomy approach, modified Denker's and by way of a canine fossa trepanation [13]. During surgical planning for cyst enucleation, surgeons should consider choosing the appropriate endoscopic approach.…”
mentioning
confidence: 99%
“…Recent studies have reported gender-specific differences in the feasibility of a PLWA (42) . Andrianakis et al (42) reported a greater distance (1.5 mm (95% CI 0.8-2.2) between the lacrimal system and the anterior maxillary wall in males compared to females.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, females may potentially face an increased risk of intra-and post-operative morbidity due to problems caused by surgery during a PLWA (42) .…”
Section: Discussionmentioning
confidence: 99%
“…Even with short distances, modifications to the technique involving the removal of the bony nasolacrimal canal and mobilisation of the NLD to create an adequate working channel have been described in the literature [ 20 , 21 , 31 ]. There is variability among the population in the length of this bony window, with gender differences reported in some studies, with females having shorter distances and greater surgical complexity in accessing the anterior maxillary sinus [ 32 ].…”
Section: Discussionmentioning
confidence: 99%